Periodic Inspection Program of Nuclear PWR reactor Pressure Vessel (Brazilian Journal of Radiation Sciences, 2021)
This work aims to present a methodology that guides the operating organization to carry out periodic inspections in the nuclear PWR reactor pressure vessels. At first, fundamental concepts of nuclear energy and their application were discussed. This discussion allowed the presentation of: functions and characteristics of PWR reactor pressure vessels and the understanding of damage and effects of irradiation in the materials used in the manufacture of these vessels. From the recommendations of codes and publications related to pressure vessel integrity and inspections, for nuclear applications, the minimum requirements that should be considered in the inspection program preparation for this equipment were established. Furthermore, this paper shows the advantages of using computational tools to manage inspection results allowing the operators to plan and monitor the activities for the maintenance so as to avoid financial loss and environmental damage.